2023
DOI: 10.1039/d2dt03508a
|View full text |Cite
|
Sign up to set email alerts
|

A naphthalene-based heterobimetallic triazolylidene IrIII/PdII complex: regioselective to regiospecific C–H activation, tandem catalysis and a copper-free Sonogashira reaction

Abstract: Heterobimetallic complexes featuring mesoionic carbene (MIC) donor ligands are gaining enormous popularity in tandem catalysis owing to the combined action of two different metal centers during catalysis. A rare version...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Complex R ‐[ 4 ] also exhibits higher catalytic activity as compared to previously reported complex C (Figure 1). [17] Comparing the catalytic outcomes of complex R ‐[ 4 ] with other Pd II NHC/PPh 3 complexes, it was observed that the catalytic activity of R ‐[ 4 ] is comparable to that of a highly active trinuclear Pd II complex [18b] and in some cases even higher under copper free conditions [6d,e,25c] . The better catalytic outcomes of complex R ‐[ 4 ] over complex R ‐[ 3 ] were correlated with their redox behaviour obtained from electrochemical measurements.…”
Section: Resultsmentioning
confidence: 83%
“…Complex R ‐[ 4 ] also exhibits higher catalytic activity as compared to previously reported complex C (Figure 1). [17] Comparing the catalytic outcomes of complex R ‐[ 4 ] with other Pd II NHC/PPh 3 complexes, it was observed that the catalytic activity of R ‐[ 4 ] is comparable to that of a highly active trinuclear Pd II complex [18b] and in some cases even higher under copper free conditions [6d,e,25c] . The better catalytic outcomes of complex R ‐[ 4 ] over complex R ‐[ 3 ] were correlated with their redox behaviour obtained from electrochemical measurements.…”
Section: Resultsmentioning
confidence: 83%
“…The bis-triazolium salt could be deprotonated in a stepwise manner, such that its reaction with [IrCl 2 (Cp*)] 2 in the presence of Cs 2 CO 3 , NaOAc, and KI in acetonitrile led to selective monometalation, yielding the cyclometalated Ir-NHC complex 118 (Scheme 41). The subsequent metalation of the other triazolium fragment of the molecule with PdCl 2 in pyridine in the presence of K 2 CO 3 and KI provided the heterobimetallic (Ir/Pd) bis(triazolylidene) complex 119 [63]. The analogous homobimetallic Pd/Pd complex 120 could be obtained in one step from the bis-triazolium salt.…”
Section: Synthesis and Catalytic Application Of Heterobimetallic Nhc ...mentioning
confidence: 99%
“…Another method involves the use of specific metal moieties as metalloligands to house the second metal center. This approach has afforded two electron mixedvalent {Rh Ι ,Rh ΙΙΙ } 21 and {Ir 0 /Ir ΙΙ } 22 complexes, heterometallic {Ni ΙΙ ,Ru ΙΙ } 16 and {Ir ΙΙΙ ,Pd ΙΙ } 23 cores, as well as the trinuclear {Ni 0 -V-Ni ΙΙ } structure. 24 Other alternatives such as comproportionation, ligand addition, and reductive elimination reactions have also been applied successfully.…”
Section: ■ Introductionmentioning
confidence: 99%